Plasticizers and BPA Residues in Tunisian and Italian Culinary Herbs and Spices - Di Bella, Giuseppa; Ben Mansour, Hedi; Ben Tekaya, Asma; Beltifa, Asma; Potortì, Angela Giorgia; Saiya, Emanuele; Bartolomeo, Giovanni; Dugo, Giacomo; Lo Turco, Vincenzo (Journal of food science, 2018)
In the present study, 18 plasticizers and residues in 10 different Tunisian and Italian culinary herbs and spices (black pepper, mint, caraway, coriander, oregano, rosemary, thyme, fennel, verbena, and laurel) were determined by GC/MS. Di‐methylphthalate, di‐(2‐methylpropyl)adipate, di‐n‐butyladipate, di‐propylphthalate, benzylbenzoate, di‐phenylphthalate, and bisphenol A were lower than their LOQ in all 118 samples. Among the Tunisian samples, di‐(2‐ethylhexyl)phthalate was found in all types of samples and di‐butylphthalate in 50% of types; all other phthalates were rarely dectected. Among the adipates, only di‐methyladipate was found in 90% of types; di‐ethyladipate was seldom found and di‐(2‐ethylhexyl)adipate only in samples of caraway. Di‐(2‐ethylhexyl)terephthalate was found in all types of samples; di‐(2‐ethylhexyl)sebacate was detected rarely but with high values. Among the Sicilian samples, di‐ethylphthalate and di‐(2‐methylpropyl)phthalate were detected only in samples of mint; di‐methyladipate, di‐butylphthalate, and benzylbutylphthalate were identified in oregano and laurel; di‐(2‐ethylhexyl)terephthalate and di‐(2‐ethylhexyl)sebacate only in oregano. In any case, the results suggested that intake of these contaminants through spices and herbs is not a dangerous risk to the consumers. Probably, as already observed for the other food, these contaminants could result from pollution of the environment (air, water, and/or soil) and/or farming methods. Practical Application Plasticizers and BPA in Tunisian and Italian spices were determined by GC/MS. Tunisian spices seem to contain more residues than Italian samples. Intake of these contaminants by spices is not a dangerous risk to the consumers. These pollutants could result from environmental pollution or agricultural practices.